Translator's Liberty and Originality: Reexamining the Concepts in the Context (Global Journal of Human-Social Science, 2019)
Translation is very familiar, but a very complex activity. Therefore, the role of the translator is not a very easy one. More significantly, the translator, in the act of translation, is constantly in a state of making choices between two dissimilar systems to reach an unattainable balance point (called the equivalence). In spite of such a difficult nature of the task, the role of the translator is one of the most undervalued ones. Ideally, a translator is expected to represent the source text exactly and yet, in doing so, he/she is robbed of another supreme quality of a creative artist-'originality'. Within this context, this paper aims to explore the extent of liberty practiced by the translator and reexamines the concept of originality related to this.
Keywords: ranslation; translator; translator’s liberty; translators’ originality; source text; creative agency